Stirling Engine and absolute sealing - Raballand Thierry (EDP Sciences, 2021)
Referring to the sketches, the alternative rotation of shaft (101) allows for absolute sealing between the left side and the right side of seal (1020). A device for total sealing around a shaft in alternating rotation is characterized in that a seal (1020), the main part of the device, called a torsion disc, constitutes the material insulator and is fixed on a shaft (101) by means of two spacers (610) and (620), where the spacer (610) is held in position by the bearing (710) and the spacer (620), which clamps the seal (1020), is held in position by the bearing (720). Along the shaft (101) on both sides of the seal (1020), O-rings (510) and (520) and possibly temperature insulating rings (410) and (420) can be arranged. On both sides of the seal (1020) there are possibly two pressure isolating stops (210) and (220), which slide in rotation on two other stops (110) and (120). The two bearing housings (228) and (8) are positioned relative to each other by means of shims (7) in order to clamp the seal (1020) at the bore and at the shaft. Connecting screws connect the bearing housings (228) and (8) and further connecting screws connect the housing (8) and the wall (22). Absolute sealing of a kinematic Stirling engine is now achievable. A French patent was taken out on August 27th, 2020.